1972
DOI: 10.1128/iai.6.6.899-904.1972
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytosis-Promoting Factor of Bordetella pertussis I. Purification and Characterization

Abstract: The leucocytosis-promoting factor was purified from the supernatant fluid of spent cultures of Bordetella pertussis on solid medium. After precipitation at 67% saturation of ammonium sulfate, the leucocytosis-promoting factor was extracted with a 1.0 M NaCl solution. Purification was accomplished by starch block electrophoresis and sucrose density gradient centrifugation. The purified preparation contained a high leucocytosis-promoting activity, and as small an amount as 0.04 ,ug of protein induced leucocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

1976
1976
1999
1999

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 19 publications
3
29
0
1
Order By: Relevance
“…Differential centrifugation strongly suggested that the hemagglutinating properties did reside in the filamentous particles. These results are consistent with the findings of Sato and his colleagues (26)(27)(28) but they also suggested that the filaments were identical with LPF and HSF, an observation that is not confirmed by the present studies. They also proposed that the filaments can induce protection against experimental pertussis, an observation which preliminary results in our laboratory tend to verify.…”
Section: Phase I Cells Of B Pertussis and Their Products Induce A Nusupporting
confidence: 89%
See 1 more Smart Citation
“…Differential centrifugation strongly suggested that the hemagglutinating properties did reside in the filamentous particles. These results are consistent with the findings of Sato and his colleagues (26)(27)(28) but they also suggested that the filaments were identical with LPF and HSF, an observation that is not confirmed by the present studies. They also proposed that the filaments can induce protection against experimental pertussis, an observation which preliminary results in our laboratory tend to verify.…”
Section: Phase I Cells Of B Pertussis and Their Products Induce A Nusupporting
confidence: 89%
“…pertuss/s which had LPF as well as HSF activity and which contained greater than 50% lipid (16). In their filament-rich preparations with LPF activity Sate and Arai (26) also reported the presence of 17.5% lipid, and Munoz and Hestekin (31) found 28.4% lipid in partially purified HSF, but in these cases the products were clearly heterogenous.…”
Section: Phase I Cells Of B Pertussis and Their Products Induce A Numentioning
confidence: 94%
“…Arai and Sato (3) called these fimbrial HA (FHA) and leukocytosis-promoting factor HA. These substances were separated from leukocytosis-promoting factor preparations previously thought to be pure (28)(29)(30). Arai and Sato (3) and Sato et al (31) showed that FHA was nontoxic and protected mice from i.c.…”
mentioning
confidence: 99%
“…The bacterial strains used In this work were: S. perfuss/'s Tohama, 1.2 serotype (Sato and Arai. 1972); B. pertussis H36 1.3 serotype and B. parapertussis M/S180, N. Preston; E. co// DH5, end1A^.…”
Section: Bacterial Strains Piasmids and Mediamentioning
confidence: 99%